Analisis Hukum Islam Terhadap Praktek Jual Beli Buah Melon Dengan Sistem Tebas - Nurul Inayah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2018)
The economic development at the present time have a lot of emerging practices and selling a wide variety of them is the practice of buying and selling melon with a slash that occurred in the village of Buluagung. The practice of buying and selling are farmers engaged in transactions with slasher when the melon is already visible and yellowed, but not worth the harvest with the provision of an advance as a sign. After the transaction, the indirect slasher the melon harvest, but wait until the melon is already a decent harvest. And that's when freshly picked melons slasher already bought once on payment. This type of research is descriptive qualitative research, the research aims to match the arguments of the sale and purchase practices of slash in the village Buluagung resulting in the law in question. This study aims to determine how the practice of buying and selling melon with a slash in the village Buluagung District of Siliragung Banyuwangi, and knowing how the analysis of Islamic law against the cult of selling melon with a slash in the village Buluagung subdistrict Siliragung district of Banyuwangi is in conformity with the law Muamalah in Islam. In this study data collection using interviews, documentation, and observation. In this study, researchers analyzed data obtained by means of an interactive model consisting of three components, namely the collection of data (data collection), the reduction of the data (data reduction), presentation of data (data display), the conclusion and the data ferifikasi (conclusion and verifying). The results of the research are buying and selling rice in the village buluagung slash is valid under Islamic law analysis, because in accordance with the pillars and the terms of buying and selling, namely: Ä€qidain, Ma'qÅ«d 'alaih and sighat (Islamic marriage contract) and to avoid several possible facades, such as gharar, Riba, a transaction in two intents and utilization and maintenance of land by the buyer.